Hip arthroscopy for femoroacetabular impingement (FAI) patients with self-reported allergies: do multiple allergies have an effect on outcome?. Issue 4 (25th October 2019) - Ramos, Nicholas; Gerhardt, Michael; Banffy, Michael
Abstract: Multiple self-reported allergies have been reported as a prognostic factor for outcome the following orthopedic procedures. This relationship has not yet been evaluated in a hip arthroscopy population. The purpose of this study is to identify associations between allergies and post-operative outcome scores in patients undergoing hip arthroscopy for femoroacetabular impingement (FAI). A retrospective review of surgically treated FAI patients at our institution was performed. Patient-reported allergies and 6-month and 1-year modified Harris Hip Scores (mHHS) were recorded. Bivariate analysis was performed evaluating association between allergies and post-operative mHHS. Multivariate regression was used to identify independent factors associated with post-operative mHHS while controlling for age, sex, BMI, psychiatric comorbidity, symptom duration, labral repair versus debridement, capsular management, chondral lesions and use of adjunct platelet rich plasma (PRP). Seventy patients were analysed. Average age was 30.7 years old (SD 8.96). A 52.9% were females. Twenty-six patients (37.1%) had reported allergies. At 6 months, bivariate analysis demonstrated no significant association between allergies and postop mHHS. This was true comparing patients with 0 versus 1 versus 2 versus 3 versus 5 allergies as separate groups (medians from 83.1 to 91.0, P = 0.60) as well as when combining patients with >2 allergies into one group (0 versus 1 versus 2–5 allergies) (medians 84.7, 83.1, 86.0, respectively, P = 0.328). At 1 year, this lack of association was more pronounced (0 versus 1 versus 2 versus 3 versus 5: medians from 87.0 to 93.5, P = 0.9265 and 0 versus 1 versus 2–5: medians 93.5, 91.7, 89.0, respectively, P = 0.6450). Linear regression demonstrated preop mHHS and age were significantly associated with 1-year mHHS (logit mHHS rate = 0.026 ± 0.008 per unit, P = 0.0014 for preop mHHS and logit mHHS rate=−0.061 ± 0.018 per year, P = 0.0010 for age). After controlling for age and preop mHHS, allergies were not associated with postop mHHS. Allergies demonstrated no association with post-operative outcome following surgical treatment of FAI.